Toll like receptor 2(TLR2) in acne vulgaris patients before and after oral isotretinion therapy - Mahmood, Wakas Saadi (AL-Kindy College Medical Journal, 2019)
Background: Acne vulgaris is one of the top three most commonly encountered dermatological problems worldwide in both primary and secondary care. Human keratinocytes express functional TLR2 heterodimers. An increased expression of TLR2 was detected in the epidermis of inflammatory acne lesions, as observed in normal skin; the expression level increased with the degree of differentiation of the keratinocytes. TLR2 expression is upregulated in inflammatory acne lesions and induced by C. acnes. The current study conducted to assess the oral isotretinion treatment effect on the acne vulgaris patients by  evaluated the Toll Like Receptor 2 as a major  immune system marker in Acne vulgaris immune response. Methods: 50 patients with acne vulgaris seen in  outpatient clinic of dermatology centre(Al-Baidhaa out clinic center) in Baghdad during the period 1/9/2017 to 1/8/2018. The  diagnosis of patients were done by the specialist dermatologist only sever and moderate acne cases were chosen. Fifty serum  samples were collected before oral isotretinion therapy, only forty-five serum samples were collected after 8 weeks of oral isotretinion therapy. All patients have received 0.5mg-1mg/kg/day of oral isotretinoin. The mean ages was 22 years(range, 16-36 years). A total of 50 patients, 36(72%) of patients were females and 14(28%) were males. Furthermore 43(86%) of cases have heredity history. Also control serum samples were collected from people without acne and they chose with the same mean ages. The serum samples were stored at -70°C for up to six months. ELISA test for quantitative determination of TLR2 human was done. Statistical analysis was done using T-test.Results: Highly significant statistical difference were noticed (p